A survey of hospital food service in the Greater Manila area - Buenaventura, Martha Elizabeth Mauricio
This is a survey of food service in 49 hospitals with a minimum bed capacity of 75 in the Greater Manila Area licensed by the Bureau of Medical Services of the Department of Health as of July 1973. Data were obtained from the hospital administrator, the head of the food service unit, and the personnel officer by means of a questionnaire. General Characteristics of the Hospital and the Food Service Information on the hospital was based on the responses of 14 government and 33 private institutions. Forty were general and seven were special hospitals. Government hospitals were larger, had higher mean number of beds in charity wards, and had higher occupancy rates. The rates charged for room accommodations were higher in private than in government hospitals. Among the 49 food services studied, 48 were operated by the hospital; one, by a concessionaire. The most common term used to refer to the food service unit was dietary department. A greater number of hospital administrators and heads of food service units in government hospitals practiced better management procedures of their units than those in private institutions in terms of disseminating hospital and departmental objectives to hospital employees. The former also had available organizational charts and written job descriptions. The most common services rendered by the dietary department were the preparation and service of meals, diet instruction to patients, and nutrition information to medical and paramedical students. In a hospital, the areas of responsibility of a dietitian or nutritionist were in food service administration, therapeutics, and education. Dietitians and nutritionists in government hospitals were assigned fewer areas of responsibilities as compared to those in private institutions. Most of the tasks performed by food service workers were similar to those in the job description by the WAPCO. However, there were some specialized tasks not included in the WAPCO job descriptions that food service workers performed. Food Services: Patient and Non-patient The mean number of patient meals served per day was higher in government than in private institutions. On the other hand, the mean number of non-patient meals served per day was higher in private as compared to government hospitals. The most commonly served modified hospital diets were modified sodium, bland, diabetic, and modified cholesterol diets. Menus planned for patients and non-patients were pre-dominantly nonselective. The menu patterns of meals for pay patients were more extensive than those for charity patients. In a hospital, food preparation and distribution may be centralized or decentralized. A centralized method of food preparation and distribution was used in most hospitals. Personnel There were 1,483 food service employees in the hospitals studied. Majority of these employees were food service workers. The mean percentage of hospital employees assigned to the food service ranged from five to ten percent. Most government hospitals used the WAPCO classification of job positions. The private hospitals did not have a common classification of positions in the dietary department. To meaningfully compare existing positions in hospital food service, the positions were grouped into dietitians and nutritionists, cooks, food service workers, and other kitchen workers. The actual mean starting salary for positions in food service units of government hospitals were higher than those for private institutions. Regardless of ownership, dietitians received higher starting salaries than nutritionists; and heads of food service units received higher starting salaries than non-heads. Compared to non-supervisory cooks, supervisory cooks received higher starting salaries. Fringe benefits given to food service employees in government and private hospitals were comparable. Employee turnover in the dietary department was 7.32 percent for private and 0.99 percent for government hospitals. Regardless of ownership, turnover was highest for dietitians and nutritionists, 19.70 percent. Specific reasons for employee termination and resignation were obtained. Very few hospitals provided training for food service employees. The study provides bases for setting up training programs and improvement of selected aspects of food service in hospitals.